2015
DOI: 10.1007/s00264-015-3014-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of post-operative malalignment in fixed-bearing medial unicompartmental knee arthroplasty

Abstract: Attention should be given to the possibility of post-operative malalignment during medial UKA in patients with a greater varus angle in pre-operative DFVA, TBVA and valgus stress angle, especially with a greater varus DFVA, which was the strongest predictor for malalignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Several authors examined the correlation between the BMI and UKA survival (10,11,(16)(17)(18)(19)(20)(21). As far as we know, this study is the first to examine which component's malalignment has an effect on medial UKA survival and long-term clinical outcome in obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors examined the correlation between the BMI and UKA survival (10,11,(16)(17)(18)(19)(20)(21). As far as we know, this study is the first to examine which component's malalignment has an effect on medial UKA survival and long-term clinical outcome in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors' opinion is that the reason for failures is component malalignment such as varus-valgus component malalignment (3,10,11), more than 6 degrees of intraprosthetic divergence, more than 3 degrees of change in tibial component's obliquity and 2 degrees of cange of TS (4). Chatellard (4) reported that more than 2 mm of prosthetic joint space elevation or depression and more than 5 degrees of residual varus deformity both lead to mechanical failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahn et al noted the likelihood of post-operative malalignment during medial UKA in patients with a greater varus angle in pre-operative distal femoral varus angle (DFVA), tibial bone varus angle (TBVA), and valgus stress angle, particularly with a greater varus DFVA, which was the strongest predictor for malalignment. 70 …”
Section: Complications Of Ukamentioning
confidence: 99%
“…Therefore, a reproducible method of predicting postoperative coronal alignment is desired to assume the risk of postoperative coronal malalignment. However, only a few studies have reported the risk factors of postoperative coronal malalignment in UKA [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%